2019
DOI: 10.1016/j.jstrokecerebrovasdis.2019.05.019
|View full text |Cite
|
Sign up to set email alerts
|

Electroencephalography Measures are Useful for Identifying Large Acute Ischemic Stroke in the Emergency Department

Abstract: Background: Early diagnosis of stroke optimizes reperfusion therapies, but behavioral measures have incomplete accuracy. EEG has high sensitivity for immediately detecting brain ischemia. This pilot study aimed to evaluate feasibility and utility of EEG for identifying patients with a large acute ischemic stroke during Emergency Department evaluation, as these data might be useful in the pre-hospital setting. Methods: A 3-minute resting EEG was recorded using a dense-array (256-lead) system in patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 34 publications
1
41
0
Order By: Relevance
“…Electrophysiological and neuroimaging measures together more accurately predict stroke symptoms than neuroimaging alone 6,7,41 . Indeed, a recent study of suspected stroke cases has demonstrated that delta band power and alpha/delta frequency ratio of EEG recorded in the emergency department using a dense-array (256 lead) system could predict large stroke damage 42 . Other studies [43][44][45][46][47][48] have identified potential EEG biomarkers of clinical status or motor impairment, and even to predict recovery in the period after stroke 44,49 .…”
Section: Discussionmentioning
confidence: 99%
“…Electrophysiological and neuroimaging measures together more accurately predict stroke symptoms than neuroimaging alone 6,7,41 . Indeed, a recent study of suspected stroke cases has demonstrated that delta band power and alpha/delta frequency ratio of EEG recorded in the emergency department using a dense-array (256 lead) system could predict large stroke damage 42 . Other studies [43][44][45][46][47][48] have identified potential EEG biomarkers of clinical status or motor impairment, and even to predict recovery in the period after stroke 44,49 .…”
Section: Discussionmentioning
confidence: 99%
“…Intermittent rhythmic delta activity was shown to be higher in children with epilepsy [ 58 , 59 , 60 ] and Down syndrome [ 61 ]. In addition, other studies have attributed slow-wave activity to central nervous system lesions [ 62 ] and metabolic derangement appearing after stroke [ 63 , 64 ], which correlated with infarct volume [ 65 ] and brain function in this group of patients [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…The indication and utility of EEGs ordered of AIS patients is largely unknown. One study from 2019 showed that EEG performed in the ED may help identify patients with large acute strokes and may correlate with infarct volume [ 9 ], but with modern imaging techniques and interruption of stroke workflow, the utility of an EEG in ischemic stroke needs to be brought into question.…”
Section: Introductionmentioning
confidence: 99%